Exploring Challenges in Textual Translation Proficiency Among Iraqi Learners of English as a Foreign Language (EFL) - Nico, Ashur (Al-Adab Journal, 2023)
This research investigates the determinants of underperformance among students majoring in English in their textual translation skills. It delves into students' viewpoints on translation and emphasizes the influence of instructional methodologies. The study is restricted to fourth-year students at Al-Noor University College, during the academic year 2022-2023.To achieve this, a survey is conducted to gain insights from EFL learners concerning the factors contributing to subpar textual translation. A cohort of twenty-five college students is chosen for the investigation. The findings underscore that the principal obstacle to students' challenges is the employed teaching approach, coupled with inadequate time designated for translation exercises. The research underscores the necessity for heightened emphasis on translation education, specifically textual translation, as students recognize it as a potent tool for effectively conveying the culture of the target language, distinct from free and literary translation forms.